IoT Based – Smart garbage monitoring system using arduino and blynk / Muhammad Amirul Rosyad Mohd Halim - Mohd Halim, Muhammad Amirul Rosyad (2021)
Smart Garbage Monitoring System using Arduino and Blynk is an IoT-based project that is integrated with cloud computing service. It was developed specifically to help cleaners and residential college representative committee or known as Jawatankuasa Perwakilan Kolej (JPK) in monitoring the level of garbage in the dustbin through Blynk application, which makes it easy to empty the dustbin and reduce their time. This project uses ultrasonic sensor in order to measure the level of garbage in the dustbin and the data can be viewed by user through mobile application, Blynk. It will also notify user through email once the garbage bin is full. Other than notification function, Smart Garbage Monitoring System also consists of automatic open and close lid, track dustbin location and humidity level. The objectives of this project are to design the IoT based - ‘Smart Garbage Monitoring System’ that detects the level ofthe garbage displayed in an LCD attached to the dustbin and to validate the user acceptance test and functionality testing for a garbage monitoring system. The development of Smart Garbage Monitoring System used the System Development Life Cycle (SDLC) by implementing the agile model as the methodology. A user acceptance and functionality testing was conducted with 20 respondents who are the Jawatankuasa Perwakilan Kolej (JPK) and contracted cleaners to determine the effectiveness of the project by evaluating the questionnaires that were divided into four categories respectively. Results of the system evaluation showed that most of the participant were satisfied with all categories provided. Therefore, based on the features and functionality offered by the Smart Garbage Monitoring System, it will be beneficial to all users, especially contracted cleaners and JPK in UiTM Perlis.